Gerakan Sosial Perempuan Jombang (Studi Kasus di Sekolah Perempuan SEKOPER Berlian dalam Mengentaskan Diskriminasi di Ruang Publik) - Ineliyant Intan Ayu; A Zahid (Islamic Studies Journal for Social Transformation, 2023)
This study aims to see how the Jombang women's social movement minimizes discrimination in public spaces and the form of women's social movement practices through the Berlian Jombang Women's School. This research was conducted in Tambakrejo Village, Jombang. The background of this research problem by women's issues in Jombang Regency based on data from the Office for Population Control for Family Planning, Women's Empowerment and Child Protection (DPPKB PPPA) there were 145 cases in 2019, 2020 there were 142 cases, in 2021 there were 103, the cases involved women and children in the district Jombang has experienced discrimination in public spaces, including Domestic Violence (KDRT), Violence against Children (KTA), sexual harassment, extramarital affairs, incest, intimidation, trafficking, rape, and others. The method used in this research is a qualitative method with a case study approach. This type of research data comes from primary data where the data is obtained directly in the field. At the same time, secondary data comes from literature and official archives. The results of this study indicate that the form of the Jombang women's social movement within the Berlian Women's School provides a change in awareness and benefits for female school members. Such as being given entrepreneurship training, participating in socialization on gender mainstreaming, participating in comparative studies with other girls' schools, participating in cadre training in handling cases, being given parenting material, and being given an understanding of how to organize. From these several forms of practice, it shows that members of the Berlian Women's School take collective action with the aim of increasing understanding and also awareness of women in Jombang Regency.